Physical planning standard of health care facilities in the rural communities of Ondo State, Nigeria. Issue 6 (18th August 2021) - Umar, Jimoh Usman
ABSTRACT: This article examines the compliance to physical planning standards of health care facilities in the rural communities of Ondo State, Nigeria. A multi-stage sampling technique was adopted in selecting the rural communities, and quantitative and qualitative data used. The study revealed that none of the facilities met the required standard. Respondents' desired more medical personnel rather than the existence of a planning standard. The need for more medical personnel has conclusively not been met. The study recommends that compliance with planning standards should be enforced and medical personnel provided for the health care facilities.